Pharmacokinetics of erythromycin after intravenous, intramuscular and oral administration to cats - Albarellos, G. A. (2011)
The aim of this study was to characterise the pharmacokinetic properties of different formulations of erythromycin in cats. Erythromycin was administered as lactobionate (4 mg/kg, intravenously (IV)), base (10 mg/kg, intramuscularly (IM)) and ethylsuccinate tablets or suspension (15 mg/kg, orally (PO)). After IV administration, the major pharmacokinetic parameters were (mean ± SD): area under the curve (AUC)(0-∞) 2.61 ± 1.52 µg.h/mL; volume of distribution (Vz) 2.34±1.76 L/kg; total body clearance (Clt) 2.10±1.37 L/h.kg; elimination half-life (t½λ) 0.75±0.09 h and mean residence time (MRT) 0.88±0.13 h. After intramuscular administration, the principal pharmacokinetic parameters were (mean ± DS): peak concentration (Cmax), 3.54±2.16 µg/mL; time of peak (Tmax), 1.22±0.67 h; t½λ, 1.94±0.21 h and MRT, 3.50±0.82 h. The administration of erythromycin ethylsuccinate (tablets and suspension) did not produce measurable serum concentrations. After IM and IV administrations, erythromycin serum concentrations were above minimum inhibitory concentration (MIC)90=0.5 µg/mL for 7 and 1.5 h, respectively. However, these results should be cautiously interpreted since tissue erythromycin concentrations have not been measured and, it is recognised that they can reach much higher concentrations than in blood, correlating better with clinical efficacy.